2016
DOI: 10.1182/blood-2015-12-684498
|View full text |Cite
|
Sign up to set email alerts
|

The minimum required level of donor chimerism in hereditary hemophagocytic lymphohistiocytosis

Abstract: Key Points• Donor chimerism .20%-30% usually protects against late disease reactivation after day 180 post stem cell transplantation for primary HLH.• Lower levels do not inevitably result in reactivations. The risks of intervention must be weighed against the risk of reactivation.Reduced-intensity conditioning has improved survival after hematopoietic stem cell transplantation (HSCT) for hemophagocytic lymphohistiocytosis (HLH) at the cost of more frequent mixed chimerism. The minimum level of donor chimerism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 27 publications
4
61
0
3
Order By: Relevance
“…Many patients with nonmalignant disorders are symptom-free long-term after hematopoietic cell transplantation (HCT) despite mixed donor–recipient chimerism [16]. It is difficult to (1) distinguish between patients with adequate/stable donor chimerism with continued long-term disease control and those with unstable engraftment that results in disease recurrence and (2) predict the level at which donor chimerism is too low to sustain a disease-free state.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with nonmalignant disorders are symptom-free long-term after hematopoietic cell transplantation (HCT) despite mixed donor–recipient chimerism [16]. It is difficult to (1) distinguish between patients with adequate/stable donor chimerism with continued long-term disease control and those with unstable engraftment that results in disease recurrence and (2) predict the level at which donor chimerism is too low to sustain a disease-free state.…”
Section: Introductionmentioning
confidence: 99%
“…4 Based on the outcomes of HSCT in FHL patients, T-cell chimerism of at least 10% to 15% is required for efficient remission of HLH. 5,6 Hence, the T cells' transduction efficiency is a key parameter in this strategy. We demonstrated that, by using a new lentiviral pseudotype (such as the H/F-envelope), high levels of T-cell transduction can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The post-HSCT outcome in HLH patients shows that remission is maintained as long as the level of T-cell donor chimerism reaches 10% to 15%. 15,16 The conventional VSVG-LV strategy must therefore be tested in a preclinical murine model, in order to establish whether or not poor in vitro T-cell transduction prevents the achievement of this level of chimerism in vivo. Another limitation relates to the availability of T cells as a result of pancytopenia and the manifestations of HLH.…”
mentioning
confidence: 99%